Moisture Content and Protein Content of Apem Cake Based on a Composite of Purple Sweet Potato and Corn Flour - Azzahrah, Fatimah; Kurnia, Pramudya; Warajati Kisnawaty, Sudrajah (JURNAL KESMAS DAN GIZI (JKG), 2025)
Sweet potatoes and corn are local food ingredients with potential as alternative substitutes for rice. Traditionally, apem cakes are made using rice flour as the main ingredient. Partially replacing rice flour with sweet potato flour and corn flour is expected to optimize the utilization of these local ingredients and improve the nutritional value of the resulting apem cake. This study aimed to analyze the effect of using purple sweet potato flour and corn flour on the moisture content and protein content of apem cake. The study employed a completely randomized design (CRD) with four formulations of rice flour, purple sweet potato flour, and corn flour, namely A (100%:0%:0%), B (50%:15%:35%), C (50%:25%:25%), and D (50%:35%:15%). Moisture content was measured using the gravimetric method, while protein content was analyzed using the titrimetric method. Moisture content data were analyzed using Welch’s ANOVA, and protein content was analyzed using One-Way ANOVA followed by Tukey’s HSD test. The results showed that the highest moisture content was 41.42% in the formulation with 15% purple sweet potato flour and 35% corn flour, and the lowest was 40.76% in the 100% rice flour formulation. Welch’s ANOVA indicated no significant difference in moisture content among treatment groups (p = 0.378; p > 0.05). The highest protein content was 4.51% in the 100% rice flour formulation, and the lowest was 4.09% in the formulation with 35% purple sweet potato flour and 15% corn flour. ANOVA results indicated a statistically significant difference in protein content (p = 0.001; p < 0.05). In conclusion, the use of purple sweet potato flour and corn flour in apem cake did not significantly affect moisture content but significantly influenced protein content. Further investigations should focus on optimizing the formulation to evaluate the influence of the treatment on product quality and storage stability.